SISTEM KUNCI PINTU OTOMATIS MENGGUNAKAN RADIO FREQUENCY IDENTIFICATION (RFID) BERBASIS ARDUINO UNO - Mupliha; Mupliha (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2020)
The aim of this research is to: (1) devise a door lock access system automatically using RFID (Radio Frequency Identification) technology based of Arduino Uno. (2) Implement RFID (Radio Frequency Identification) lock system based of Arduino Uno.This research will be utilizing the Research and Development method (R&D) which is a criteria based developmental method where research discoveries is used to devise the product and eventually tested on the field, evaluated, and refined until it fulfils the certain quality criteria. This method has certain measures including: (1) Its potentials and problems, (2) Accumulate information, (3) Product design, (4) Product testing, (5) Product revision, (6) Trial run, (7) Product revision. Based on the test results, it can be concluded that with the use of Arduino Uno microcontroller as the central control circuit and programmed using IDE Arduino software added with RFID-MFRC522 and solenoid, which then could be used to construct an automatic door lock system by using and ID Card and to implement an automatic door lock system using Tag RFID/Reader cards as its conventional key replacement so that it could simplify and not complicate its use as it will work just from bringing it closer to a distance of 1,5 cm.